2006
DOI: 10.1038/sj.emboj.7601360
|View full text |Cite
|
Sign up to set email alerts
|

A ubiquitin ligase complex assembles linear polyubiquitin chains

Abstract: The ubiquitin system plays important roles in the regulation of numerous cellular processes by conjugating ubiquitin to target proteins. In most cases, conjugation of polyubiquitin to target proteins regulates their function. In the polyubiquitin chains reported to date, ubiquitin monomers are linked via isopeptide bonds between an internal Lys and a C‐terminal Gly. Here, we report that a protein complex consisting of two RING finger proteins, HOIL‐1L and HOIP, exhibits ubiquitin polymerization activity by rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
812
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 710 publications
(835 citation statements)
references
References 44 publications
16
812
1
6
Order By: Relevance
“…Three PUB-domain containing proteins have been described so far in humans and all interact with the p97 C-terminal tail: PNGase (peptide N-glycanase) [85,86], which is involved in the deglycosylation of misfolded glycoproteins [87], the UBX protein UBXD1 [68,85,88], and HOIP (HOIL-1-interacting protein) [89][90][91], the catalytic subunit of the E3 ubiquitin ligase LUBAC, which catalyzes the assembly of linear ubiquitin chains [92]. Molecular insights into the interaction of the PUB domain with p97 were revealed by crystal structures of the PNGase and HOIP PUB domains in complex with peptides comprising the five and four, respectively, C-terminal residues of p97 called PIM (PUB Interacting Motif) [86,91] (Fig.…”
Section: The Pub Domainmentioning
confidence: 99%
“…Three PUB-domain containing proteins have been described so far in humans and all interact with the p97 C-terminal tail: PNGase (peptide N-glycanase) [85,86], which is involved in the deglycosylation of misfolded glycoproteins [87], the UBX protein UBXD1 [68,85,88], and HOIP (HOIL-1-interacting protein) [89][90][91], the catalytic subunit of the E3 ubiquitin ligase LUBAC, which catalyzes the assembly of linear ubiquitin chains [92]. Molecular insights into the interaction of the PUB domain with p97 were revealed by crystal structures of the PNGase and HOIP PUB domains in complex with peptides comprising the five and four, respectively, C-terminal residues of p97 called PIM (PUB Interacting Motif) [86,91] (Fig.…”
Section: The Pub Domainmentioning
confidence: 99%
“…As shown by a recent study, methylation of a Cys residue in NZF domain of either TAB2 or TAB3 disrupts polyubiquitin recognition and blocks NF-jB signaling pathway [49]. Another example is HOIL-1L protein, which is a component of the linear ubiquitin chain assembly complex (LUBAC) [9]. HOIL-1L recognizes Met1-linked ubiquitin chains through its NZF domain.…”
Section: Multiple Ubiquitin-binding By a Single Ubdmentioning
confidence: 99%
“…We thus hypothesized that the ubiquitin ligase complex recognizes ubiquitin as a substrate and conjugates ubiquitin onto it to generate polyubiquitin chains. Further analyses revealed that the HOIL-1L-HOIP complex indeed generates linear polyubiquitin chains exclusively [ 4 ].…”
Section: The Linear Ubiquitin Chains and Their Roles In Nf-κb Activationmentioning
confidence: 99%
“…We have identifi ed a new type of polyubiquitin chain, the linear polyubiquitin chain, in which the carboxyl group of a ubiquitin monomer forms a peptide bond with an N-terminal Met residue of another ubiquitin molecule (Fig. 1 ) [ 4 ]. We have also identifi ed the ubiquitin ligase Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation